Short communication: Seagrass diversity and carbon sequestration: Case study on Pari Island, Jakarta Bay, Indonesia - TEGUH HUSODO; SAHBUDDIN DG. PALABBI; OEKAN S. ABDOELLAH; MOHAMAD NURZAMAN; NURULLIA FITRIANI; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2017)
Husodo T, Palabbi SDG, Abdoellah OS, Nurzaman M, Fitriani N, Partasasmita P. 2017. Seagrass diversity and carbon sequestration: Case study on Pari Island, Jakarta Bay, Indonesia. Biodiversitas 18: 1596-1601. Pari Island is located in Kepulauan Seribu chain. As a tourist destination, the seagrass ecosystem at the island is constantly under pressure from time to time. An effort to prevent widespread damage is to designate parts of the coastline as a limited access research centre. Efforts to study seagrass ecosystem on Pari Island are ongoing, including studies on seagrass' ability to sequestrate carbon. This quantitative study was conducted in December 2014. Surveys are done on the abundance and density of seagrass in 122 plots (area = 50 × 50 cm2) which spread in 6 research stations. Biomass measurements were performed by extractive method on 4 types of seagrass (Cymodocea serrulata, Halophila ovalis, Halodule uninervis and Syringodium isoetifolium). The assessment of seagrass capability in storing carbon has been done by measuring the primary productivity of above ground and below ground, while the amount of carbon released is measured from littered leaves and the leaves eaten by herbivores.The findings show that there are 7 of 12 species of seagrass identified in Indonesia, i.e. Cymodoceae rotundata, Cymodoceae serrulata, Thalassia hemprichii, Enhalus acoroides, Syringodium isoetifolium, Halodule uninervis and Halophila ovalis. The dominant species is Thalassia hemprichii (density 200±153, 261±107 and 117±52 stands/m2) and Halodule uninervis (82±59 stands/m2).Seagrass’ carbon sequestration capacity in the waters surrounding Pari Island, Jakarta Bay, is approximately 0.006-1.048 gC/m2/day whereas carbon reserves are between 0.24-346.10 gC/m2.